THE ROLE OF DISCLOSURE OF FUTURE INFORMATION IN IMPROVING THE QUALITY OF ACCOUNTING PROFITS-APPLIED STUDY IN BAGHDAD SOFT DRINKS COMPANY (World Economics and Finance Bulletin, 2025)
The research aims to study the cognitive foundations of both future information and the quality of accounting profits, as well as the role of disclosure of future information in improving the quality of accounting profits, as the clarity of management policies helps to improve the predictability of the future financial situation, which leads to the efficiency of future decisions, especially if management can justify its views and future assumptions. Research applied in Baghdad Soft Drinks Company. It is a company for the production and marketing of soft drinks in Iraq. The company has an exclusive license to sell Pepsi products in Iraq. The research for the years (2021-2024) was applied. The research reached several conclusions, the most important of which was that the quality of accounting disclosure of future information depends on the extent to which the company adopts good governance mechanisms, and accordingly, the quality of governance mechanisms is important in improving the quality of accounting disclosure of future information, financial and non-financial information, and the risks faced by the company and how to face them, which is reflected in enhancing the confidence of stakeholders in financial reports.
Keywords: information; company; accounting profits; assumptions